(untitled) (Research, Society and Development, 2021)
This literature review aimed to evaluate the use of rotary file systems compared to standard manual file systems, taking into account the time and quality of root canal preparation in primary teeth, as well as the effect of treatment with these files on cooperation and the development of postoperative pain in children. The bibliographic survey was based on articles published in the last 5 years, found in the following databases in the health area: PubMed/Medline, Scopus, LILACS, SciELO and Cocrhane. The results showed that endodontic treatments with rotary files exhibited shorter time and better quality of the biomechanical preparation of the canals in primary teeth, as well as resulted in less experience of postoperative pain, when compared to the use of manual files. Based on this, it is possible to conclude that pulpectomies performed with rotary files are effective, safe and reduce treatment time and postoperative pain in pediatric endodontic treatment.